Effect of Rhodiola rosea L. roots extract on pain perception in humans. - Bożena Antkowiak; Oktawiusz Antkowiak; Marek Brytan; Paweł Cięszczyk; Ewa Szarska; Ryszard Puchała; Magdalena Ciechanowska; Magdalena Łapot; Izabela Winnicka; Ewelina Maculewicz (Elsevier, 2022)
Background: Rhodiola rosea L. (Crassulaceae) is one of the better known plant adaptogens possessing unique protective properties against various harmful environmental factors. Among the numerous pharmacological effects of R. rosea extracts (RRE) and their active compounds, antinociceptive activity has previously been demonstrated in experimental studies. Purpose: The study was aimed to evaluate the effect of a single, high dose of RRE on pain perception induced by diverse nociceptive stimuli in healthy volunteers. Material and methods: The study was designed as a double blind, placebo-controlled trial. Each participant underwent the trial after both placebo and RRE administration. The order of trials was randomly assigned to the participants. The threshold and tolerance to heat and pressure stimulus and cold water tolerance (cold pressor test) were assessed in a group of 142 volunteers aged 19-27 years. The subjects were tested in three subsequent trials in one-week intervals. Baseline measurements were followed by tests after a single, oral intake of hydroethanolic RRE capsules (50 mg/kg) or placebo (PL). Measurement results were analyzed for the entire study group and subgroups characterized by high and low pain sensitivity (≤ 25 and ≥ 75 percentile, respectively). Results: After intake of a single dose of RRE, both pain threshold (RRE 350.5 ± 115.4 kPa vs. PL 329.4 ± 117.4 kPa; p < 0.01) and pain tolerance to pressure (RRE 1160 ± 333.3 kPa vs. PL 1119 ± 347 kPa; p < 0.05) were significantly higher compared to placebo in the entire study group. Similar effects on pressure pain threshold were shown in the subgroup with high pain sensitivity (RRE 274.3 ± 85 kPa vs. PL 240.8 ± 75.2 kPa; p < 0.01). However, the mean differences between trials do not exceed the calculated values of the minimum detectable change (MDC95). RRE had no substantial effect on thermal pain perception (contact heat and cold water) either in the entire group or in the high and low pain sensitivity subgroups. Conclusions: Application of a single, high dose of RRE does not modify response to thermal pain (heat, cold water), but may attenuate perception of mechanical pain in young, healthy individuals, especially those with high pain sensitivity. Further studies are warranted to confirm the clinical significance of the observed effects and to determine the influence of RRE on pain perception in the general population.